AN EVALUATION STUDY OF COMMUNITY KNOWLEDGE AND ATTITUDES TOWARDS SAFE, HEALTHY, SHADY VILLAGES IN PURWODADI VILLAGE, KUALA PESISIR SUB-DISTRICT, NAGAN RAYA DISTRICT - Andes Aboni; Chairul Amri; Ladani; Laili Rahmawati; Aulya Fazira; Syarifah Putri Nabila (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The study in Purwodadi Village, Aceh, assessed the DESA ASRI program's impact on community health and environmental awareness. Utilizing socialization and focus group discussions, the research significantly enhanced the community's understanding of DESA ASRI. Pre-tests and post-tests demonstrated substantial knowledge growth and positive attitude shifts. Most respondents now actively support DESA ASRI's role in addressing health and environmental concerns. Socialization efforts prompted widespread community participation in waste management innovations, highlighting the program's effectiveness.These findings underline the vital role of education and socialization in improving health, environment, and waste management in challenging areas. They emphasize the success of initiatives like DESA ASRI in transforming community perspectives and behaviors. The study's outcomes suggest that community-focused programs, supported by educational approaches, are pivotal in addressing health and environmental issues. DESA ASRI serves as a model, showcasing the potential impact of targeted socialization and educational strategies. These insights contribute significantly to the ongoing efforts in enhancing health, environmental awareness, and sustainable waste management practices in communities facing similar challenges.